Kemampuan Berpikir Reflektif Matematis Siswa dalam Menyelesaikan Permasalahan Sistem Persamaan Linear Dua Variabel (SPLDV) - Febrianty, Eritha Dewi; Herman, Tatang; Suhendra, Suhendra; Mardliyah, Syifa; Pauji, Ikbal (Edumatica : Jurnal Pendidikan Matematika, 2024)
Mathematical reflective thinking ability is one of the higher-level abilities that can support other mathematical thinking skills. Therefore, ensuring students have good mathematical reflective thinking skills is essential. This study aimed to analyze students' mathematical reflective thinking skills (KBRMS) on the material of a two-variable linear equation system (SPLDV). This research approach is qualitative with a phenomenological type. Data collection techniques were carried out through reflective thinking skills tests and interviews. The study subjects were grade VIII junior high school students who had studied SPLDV material using purposive sampling techniques. Data analysis techniques in this study are data reduction, data display, conclusions, and verification. This mathematical reflective thinking ability analysis is based on indicators of mathematical reflective thinking ability, namely reacting, elaborating, and contemplating. The results of this study show that students can master reacting and elaborating indicators when faced with problems they usually encounter. In contrast, for contemplating indicators, students still experience difficulties when faced with problems different from those traditionally exemplified, such as difficulties in understanding problems and determining the concept of the material used. Based on this, it is shown that students' mathematical reflective thinking skills have not been fulfilled optimally.